The Empty Bower and the Lone Fountain - Domenic Leo (Perspectives Médiévales)
French poet-composer Guillaume de Machaut’s complete-works manuscripts are illuminated with hundreds of miniatures. Two manuscripts, made in his lifetime (c. 1300-1377), are among the most luxurious (BnF, ms. fr. 1584; BnF, ms. fr. 1586). I propose separating the iconographic programs from two dits (long, narrative poems cast in the first person) in these manuscripts to ‘analyze’ the resulting paratexts; perhaps anachronistic, but ultimately instructive in reconstructing period reception. This problematizes the role of the iconographer and his degree of responsibility in the creation of the images and/or their ‘arrangement’ within the text. Such an approach questions the concept of the supremacy of the text. Must an iconographic program only be judged by its rapport with the text? Can there be ‘right’ or ‘wrong’ ways in which the image is inserted into the text? Sixten Ringbom describes text-image bonds that are pertinent to understanding Machaut’s textual “Je” and the iconographer’s depiction of him. On occasion, the narrator disappears from the miniatures and the object of his gaze, unites the viewer, if only momentarily, with him – a static, visual ekphrasis. They constitute a form of ‘communication’ in and of themselves projected in a temporal stream of meaning. The concatenative sequence, hinging on discrete narratives, can be analyzed as a group. Subsequently the links can be removed, enabling an analysis of individual images. I will apply this methodology to the iconographic programs from Le dit dou vergier and La fonteinne amoureuse. The frontispiece for the Vergier depicts a large, intricately painted empty bower; the narrator is ancillary to this central image and stands off to one side. In the Fonteinne, two images of a fountain as subject matter, devoid of figures, break the narrative flow. This literally forces the viewer to focus on the subject matter rather than passively following the verbal action taking place around it. The goal of this study, then, is to reconsider the text as a means for interpreting the ‘correctness’ of the placement or content of the miniatures and to explore the inverse; c’est-à-dire, la théorisation de l’erreur.